2019
DOI: 10.2337/db18-0290
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide Association Study of Incident Type 2 Diabetes in a British Population: EPIC-Norfolk Study

Abstract: Epigenetic changes may contribute substantially to risks of diseases of aging. Previous studies reported seven methylation variable positions (MVPs) robustly associated with incident type 2 diabetes mellitus (T2DM). However, their causal roles in T2DM are unclear. In an incident T2DM case-cohort study nested within the population-based European Prospective Investigation into Cancer and Nutrition (EPIC)-Norfolk cohort, we used whole blood DNA collected at baseline, up to 11 years before T2DM onset, to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 55 publications
8
108
2
2
Order By: Relevance
“…Furthermore, PTPRN2 (receptor-type tyrosine-protein phosphatase N2), one of the top five predictive genes in our study, is required for the accumulation of normal levels of insulin-containing vesicles, preventing their degradation, and plays a role in glucose-stimulated insulin secretion ( 37 ). None of our 105 candidates were genome-wide statistically significant in the two largest prospective epigenetic-wide association studies ( 38 , 39 ). In a nested case-control study, Chambers et al ( 39 ) identified an association between differential methylation at five genetic loci ( ABCG1 , PHOSPHO1 , SOCS3 , SREBF1 , and TXNIP ) with T2D incidence among Indian Asians and Europeans.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, PTPRN2 (receptor-type tyrosine-protein phosphatase N2), one of the top five predictive genes in our study, is required for the accumulation of normal levels of insulin-containing vesicles, preventing their degradation, and plays a role in glucose-stimulated insulin secretion ( 37 ). None of our 105 candidates were genome-wide statistically significant in the two largest prospective epigenetic-wide association studies ( 38 , 39 ). In a nested case-control study, Chambers et al ( 39 ) identified an association between differential methylation at five genetic loci ( ABCG1 , PHOSPHO1 , SOCS3 , SREBF1 , and TXNIP ) with T2D incidence among Indian Asians and Europeans.…”
Section: Discussionmentioning
confidence: 89%
“… 38 39 Inversely, overexpression of CPT1A in the liver of obese mice reduces inflammation and improves insulin signaling. 40 Recently, epigenome-wide association studies have disclosed the causal role of CPT1A methylation in type 2 diabetes 41 and the association between intron 1 CPT1A methylation and gestational BMI. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that DNA methylation in blood is associated with future risk of T2D using prospective population‐based cohorts [13,66,74,75]. Methylation of the ABCG1 , PHOSPHO1 , TXNIP and CPT1 locus could be replicated in independent prospective cohorts.…”
Section: Can Epigenetics Be Of Clinical Use In Diabetes?mentioning
confidence: 98%
“…Some studies have taken on the challenging task to examine if epigenetic mechanisms may cause T2D. These studies have used both mathematical modelling such as causal inference tests (CITs) and Mendelian randomization analyses as well as experimental approaches including epigenetic editing [64‐67] (Fig. 3a).…”
Section: Do Epigenetic Modifications Cause T2d?mentioning
confidence: 99%
See 1 more Smart Citation